Natural language processing with Python - Bird, Steven; Klein, Ewan.; Loper, Edward (Beijing ; Cambridge [Mass.] : O'Reilly, 2009)
This is an introduction to natural language processing, which supports a variety of language technologies, from predictive text and email filtering to automatic summarization and translation.
"Analyzing text with the natural language toolkit"--Cover.
Includes bibliographical references (p. 449-458) and indexes.
Keywords: Python (Computer program language); Natural language processing (Computer science); Sprachverarbeitung; Python <Programmiersprache>